Turismo sexual y eventos deportivos - Beatriz Muñoz González; Borja Rivero Jiménez; Nuria García Perales (SHARE Press, 2019)
The 2006 World Cup in Germany was known as the World Cup of Prostitution. It is estimated that 10,000 girls and women were taken to Miami to sexually exploit them in the 2010 Super Bowl. This paper analyzes a phenomenon of growing interest and concern both in the field of Human Rights and social research: sex tourism linked to great sporting events. Especially serious is its connection with human trafficking networks of people, women and children. It also reviews the prevention and reporting campaigns that some NGOs have begun to develop worldwide, especially since the 2014 World Cup in Brazil